Helicobacter pylori y la patogénesis de la gastritis y la úlcera. Premio Nobel en Medicina y Fisiología. (Colombia Medica, 2006)
Helicobacter pylori y la patogénesis de la gastritis y la úlcera. Premio Nobel en Medicina y Fisiología.